Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Das, Sofia Priyadarsani; Abidin, Zaenal; Huang, Huai-Ting; Lin, Yu-Ru; Huang, Chih-Yang; Wu, Yu-Sheng; Hu, Yeh-Fang; Nan, Fan-Hua (Frontiers in Marine Science, 2024)
The health of the host is significantly influenced by the gut microbiota. Penaeus vannamei (white shrimp) is one of the most profitable aquaculture species globally. Synbiotics are typically used as a beneficial diet supplement for raising aquaculture species’ growth capacities and enhancing immunity against pathogenicity. However, the effects of synbiotics on the white shrimp intestinal microbiota remain poorly understood. In the present study, we targeted the V3–V4 region of 16S rRNA genes to analyze the effects of synbiotics on white shrimp gut microbiota. Dietary synbiotics, having Lactobacillus acidophilus, and Moringa oleifera leaf extract were added to the white shrimps’ feed in various proportions in the present study. In total, 490 operational taxonomic units yielding 23 phyla, 41 classes, 94 orders, 151 families, and 250 genera of microorganisms were obtained. The diet containing L. acidophilus at 1 × 107 CFU/g and M. oleifera at 2.5 g/kg led to an increase in the relative abundance of beneficial microorganisms through a significant decrease in the α diversity. Moreover, it upregulated several physiological pathways such as carbohydrate metabolism, signal transduction, lipid metabolism, nucleotide metabolism, amino acid metabolism, and environmental adaptation, which led to the upregulation of the AMPK, MAPK, P13K-Akt, lysosome, peroxisome, and ferroptosis signaling pathways; this enhanced growth and immunity in white shrimp. Whether a single species or a combination of different microorganisms improves growth and immunity remains unclear till now. Nevertheless, our results will facilitate further in-depth investigation into beneficial microbial communities for upliftment of white shrimp aquaculture.